Stimulation of hair growth by glucosamine sulfate and its molecular mechanisms / Farhana Abdul Rahman - Abdul Rahman, Farhana (2017)
Glucosamine sulfate is a naturally occurring amino monosaccharide which stimulates synthesis and inhibits degradation of glycosaminoglycans in synovial fluid and extracellular matrix of connective tissues. The hair papilla is a large structure at the base of a hair follicle, it is mainly made up of connective tissues. Glucosamine sulfate has been reported anecdotally, to stimulate hair growth.